SENSORY EVALUATION OF PUKIS ENRICHED WITH DIFFERENT LEVELS OF CARROT PUREE (DAUCUS CAROTA L) - T, Ratnawati; Lubis, Anwar; Permata, Inonsensia Injilia Intan; Widodo, Slamet (Yayasan Nusantara Hasana Berdikari, 2025)
This study investigates the effects of incorporating varying concentrations of carrot puree (0%, 25%, 50%, and 75%) into pukis, a traditional Indonesian snack, on its organoleptic properties. The objective is to enhance the nutritional value of pukis without compromising its sensory attributes, such as color, aroma, texture, taste, and overall acceptability. A hedonic test was conducted to assess consumer preferences for the different formulations. The results indicated that the addition of carrot puree significantly influenced the color, with higher concentrations resulting in a more vibrant orange hue. Aroma and taste were also affected, with the 25% carrot puree formulation being most preferred for maintaining the traditional flavor while offering enhanced sweetness. Texture analysis showed that the 50% carrot puree formulation provided a desirable balance between moisture retention and the light, spongy texture typical of pukis. Overall, the study found that a moderate level of carrot puree (25% to 50%) successfully enhanced the nutritional profile of pukis while preserving its sensory qualities. These findings suggest that carrot puree can be a viable ingredient for fortifying traditional snacks, offering a healthier alternative without compromising consumer acceptance.